Study of Routine Hemogram And Serum Electrolytes (Na+, K+) Changes in Malaria Patients at Tertiary Care Hospital of Western India - Surti, Hrushikesh B; Shah, Neerja H; Shah, Nailesh R (Annals of Pathology and Laboratory Medicine, 2018)
Background: Malaria is still a major health problem accounting for more than 2 million lives around the globe. This study aims to assess the routine hemogram and serum electrolytes changes enabling early detection of malaria and thereby alerts the clinician to start early treatment. Methods: A total of 325 smear positive Malaria cases at indoor and outdoor patient departments of V.S. General Hospital, Ahmedabad were analyzed by performing complete blood count (CBC) in automated cell counter and serum electrolytes estimation in biochemistry analyzer. Results were analyzed for species specificity and compared with the other relevant studies. Results: P.Vivax cases (74.8%) were more common than P.falciparum cases (25.2%) with Male predominance. Anemia (80%) and thrombocytopenia (85.8%) were most significant findings in malaria patients in routine hemogram. Mean hemoglobin was 10.3 Gram/dl; Mean Total WBC count was 6314.8/cumm and Mean Platelet count was 89628.2/cumm. Serum electrolytes showed hyponatremia (59.7%), hypokalemia (29.9%) and hyperkalemia (20.6%). All these electrolyte derangements were found more common with P.falciparum cases. Conclusions: In patients presenting with fever, low hemoglobin and platelet count must trigger high index of suspicion of malaria. Serum electrolytes should be regularly monitored in all malaria positive cases as their derangements may indicate disease severity and timely correction of it may prevent deadly complications improving morbidity and mortality in high grade infections.